PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI E-WORKSHEET TERINTEGRASI PhET MATERI GETARAN, GELOMBANG, DAN CAHAYA - Faradillah, Fariza; Tamam, Badrud; Wulandari, Ana Yuniasti Retno; Fikriyah, Aida; Wahyudhi, Sunu (Natural Science Education Research, 2025)
The problem of low critical thinking skills of students is thought to be caused by the lack of teaching materials that facilitate direct science experiments. This study aims to improve students' critical thinking skills through teaching materials that have been produced, namely e-worksheets integrated PhET. This research was conducted at SMP Negeri 4 Kamal in the 2024/2025 academic year. The type of research used is Research and Development (RD). The research design applied used One Group pretest-posttest Design. This study shows an increase in students' critical thinking skills after implementing e-worksheets integrated PhET with an average N-Gain of 0.62 which is included in the moderate criteria. The conclusion in this study is that there is an increase in critical thinking skills after learning using e-worksheets integrated PhET. The use of e-worksheets integrated PhET is very effective and innovative in learning the independent curriculum for class VIII on vibrations, waves, and light.